EFFECT OF USING POLYETHYLENE TERAPLAHATE AS SQUID FISHING AIDS IN WANGI-WANGI WATERS, SOUTHEAST SULAWESI - Hadi, Andre Pangestu; Jabbar, Meuthia Aula; Yusrizal (Jurnal Penelitian Perikanan Laut (Albacore), 2025)
Squid fishing is traditionally done in Indonesia, especially in the Eastern region such as the Wakatobi Islands. Deep sea squid fishermen on this island use hand line fishing equipment (squid fishing rods) with the help of LED lights which are still quite limited, because they only use one mini LED light with a battery that can last for 4 days. This research aims to utilize used Polyethylene Terephthalate (PET) mizone bottle waste as a squid catching tool that can be used repeatedly, as well as reusing PET waste. The research used the experimental method of fishing in Wangi-wangi waters, the lamp design used a PET waste frame using blue-green LEDs, rechargeable batteries, and was operated in water. PET waste has a hard, strong and waterproof material, this waste is used to reduce waste of used mizone bottles. This test uses three boats with sixteen repetitions. The data were analyzed using the Randomized Block Design (RAK) method. Based on the test results, different catches were obtained, where blue light was 35% (1697 fish), control light (combination of red, white, blue) was 34%, and green light was 31% (1447 fish). The calculated F value > F Table (2.92 > 2.02) which means that there is a real influence of the use of LED lights made from PET waste on fishermen catches. Key words: fishermen, LED, PET waste, squid